2004
DOI: 10.1901/jaba.2004.37-411
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Response Cost and Differential Reinforcement of Other Behavior to Reduce Disruptive Behavior in a Preschool Classroom

Abstract: This study investigated the effectiveness of response cost and differential reinforcement of other behavior (DRO) in reducing the disruptive behaviors of 25 children in a preschool classroom. Using an alternating treatments design, disruptive behavior was reduced when the participants earned tokens for the absence of disruptive behavior (DRO) or lost tokens for the occurrence of disruptive behavior (response cost). Initially, DRO was more successful in reducing the number of disruptive behaviors; however, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 4 publications
1
31
1
Order By: Relevance
“…The finding that 5-year-old children have a better performance when a response cost procedure is used (the contingent withdrawal of reinforcers; for similar results, see Conyers et al, 2004) may result from children at this age being more sensitive to a reinforcement withdrawal than are 7-year-old children, because they probably have not developed strategies and skills to handle the frustration generated by the loss of something they already possess-the secondary or primary reinforcer, in this case. We may hypothesize 1 These differences were statistically significant, F(1, 86) = 8.16, p < .01, η p 2 = .087, and F(1, 66) = 4.65, p < .05, η p 2 = .066, for the acquisition and memory test phases, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…The finding that 5-year-old children have a better performance when a response cost procedure is used (the contingent withdrawal of reinforcers; for similar results, see Conyers et al, 2004) may result from children at this age being more sensitive to a reinforcement withdrawal than are 7-year-old children, because they probably have not developed strategies and skills to handle the frustration generated by the loss of something they already possess-the secondary or primary reinforcer, in this case. We may hypothesize 1 These differences were statistically significant, F(1, 86) = 8.16, p < .01, η p 2 = .087, and F(1, 66) = 4.65, p < .05, η p 2 = .066, for the acquisition and memory test phases, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Previous research has suggested that cost and reward procedures are equally effective in reducing disruptive behavior at the individual level (Conyers et al 2004;McGoey & DuPaul, 2000;Kaufman & O'Leary, 1972) but that cost procedures are more effective in maintaining lower levels of disruptive behavior across time (Conyers et al).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has compared the direct effectiveness of different variations of token economies when administered to individual students (Boren & Colman, 1970;Conyers et al, 2004;Kaufman & O'Leary, 1972;McGoey, & DuPaul, 2000;Iwata & Bailey, 1974) however research is limited on the effectiveness of variations of token economies in conjunction with group contingencies (Lloyd, Eberhardt, & Drake, 1996).…”
Section: Token Economiesmentioning
confidence: 99%
“…It might also be useful to consider the use of response-cost (token loss) procedures to reduce inappropriate behavior. Such token-loss procedures have proven highly effective in both laboratory (Pietras & Hackenberg, 2005) and applied settings (Conyers et al, 2004;Iwata & Bailey, 1974). A simple fine or penalty may be more effective in dealing with misbehavior on the spot than the escalation of misconduct that eventually results in a time-out.…”
mentioning
confidence: 99%